Encouraging Competitive Advantage of Creative Industry Using Cluster Analysis: An Evidence from Creative Industry in Malang District, Indonesia - Sumiati Sumiati; Ainur Rofiq; Yusuf Risanto; Ida Yulianti (Department of Management, Faculty of Economics and Business, Brawijaya University, 2017)
This research investigates the condition of creative industry based on fourteen characteristics of competitive advantage including growth in turnover, transition in business, to existence of cooperative. Given the study in Indonesia, most of the creative industries in Indonesia are categorized as small medium enterprises (SME). Their sales volume, number of employees and annual profit are only at the level of small or medium business. Indonesia as a nation which has a huge numbers of SME in the world, shoud gives a bigger concern on their competitive positions Samples were taken from 200 creative industries in one of the growing area in Indonesia, Malang district. All samples represented 15 types of creative industry as regulated by Indonesia governemtn such as advertising, architecture, art, desain, etc. Data were analysed using cluster analysis. Based on agglomerative clustering, the results show that there are two clusters of creative industry in Indonesia area with low and high competitive advantage which are discussed.